Price and inventory dynamics in an oligopoly industry: A framework for commodity markets - Alexander Steinmetz (University of Würzburg, Department of Economics, 2010)
This paper analyzes the interaction between price and inventory decisions in an oligopoly industry and its implications for the dynamics of prices. The work extends existing literature and especially the work of Hall and Rust (2007) to endogenous prices and strategic oligopoly competition. We show that the optimal decision rule is an (S, s) order policy and prices and inventory are strategic substitutes. Fixed ordering costs generate infrequent orders. Consequently, with strategic competition in prices, (S, s) inventory behavior together with demand uncertainty generates endogenous cyclical patterns in prices without any exogenous shocks. Hence, the developed model provides a promising framework for explaining dynamics of commodity markets and especially observed autocorrelation in price fluctuations.
Keywords: D21; D43; E22; L81; 330; Inventory dynamics; price competition; oligopoly; (S; s) order policy; commodity markets; Lager; Preiswettbewerb; Oligopol; Spieltheorie; Bestellung; Rohstoffpreis; Volatilität; Autokorrelation; Theorie